JENIS DAN KONSISTENSI TANAH BAWAH PERMUKAAN KECAMATAN PEKALONGAN UTARA - Sonia Fauziah; Dicky Muslim; Adi Hardiyanto; Risna Widyaningrum (PPSDM Geominerba, 2022)
Pekalongan City is the northern coastal area of Java Island and is dominated by alluvial deposits. Pekalongan City’s rapid and fast development triggers much development to support the population’s need. Soil is vital in the construction of a building as a place for the erection of a building. This Paper aims to identify the type and soil consistency based on Cone Penetration Test (CPT) data. The data used amounted to 24 points, then identification of soil characteristics was carried out and map interpolation was carried out to determine the pattern of soil consistency distribution using Geographic Information System (GIS) software. The depth of the CPT test varies between 15.20 m - 20 m below the ground surface, where the qc value for a depth of 0 m - 20 m is 2.04 kg/cm2 to 138.68 kg/cm2. Based on soil classification by linking the conus resistance (qc) with the friction ratio (fr) shows the soil type in the study area, namely organic, clay, silt to sand with a very soft to hard soil consistency level.